PELATIHAN PENGENDALIAN INTERNAL PROSEDUR PENERIMAAN DAN PENGELUARAN BARANG PADA BHUMIMI KEBAYA - Utami, Ni Made Satya; Kusuma , I Gusti Agung Eka Teja; Seniati, Ni Ketut (Publika Citra Media, 2025)
Internal control in receiving and issuing goods procedures is a crucial element in maintaining the efficiency and security of a company's operations. This study was conducted at Bhumimi Kebaya, a traditional Balinese clothing company, to evaluate the effectiveness of employee training programs, the application of information technology in inventory management, and the role of internal audit. The methods used included employee training, the implementation of a technology-based management system, and routine internal audits. The results showed that all activities achieved 100% implementation, with employee training successfully improving competency and consistency in procedure implementation, information technology improving the accuracy and efficiency of record keeping, and internal audits effectively identifying weaknesses and providing recommendations for improvement. High employee participation in training and the use of technology also contributed to the success of the internal control system. These findings emphasize the importance of integrating training, technology, and audits for effective and efficient inventory management at Bhumimi Kebaya.